MANAGEMENT OF PERINEAL AND PERIANAL WARTS THROUGH AYURVEDA: A CASE REPORT - Pragna Baria; T S Dudhamal (AYUSHDHARA, 2020)
Warts are the commonest benign, viral condition found in day to day practice and it is more common in young females. In Ayurveda warts may be compared with Charmakeel. As per Acharya Sushruta Agnikarma has been described as superior para-surgical procedures among all the measures used in Ayurveda, as the disease treated by it usually did not relapse. In present case report 33 years old female patient visited in Outpatient department (OPD) of Shalya Tantra having complaints of numerous growths in perineal and peri-anal region with itching and occasional pain since 6 months. The swelling was gradually increasing in size with local itching and discomfort. So the case was diagnosed as external genital warts and Chedana (excision) of the warts with cautery was planned. Orally two tablets (500mg each) Triphala Guggulu thrice in a day with luke warm water was advised for one month. Daily cleaning with Panchavalakal Kwath and dressing with Thumari Taila was performed till complete healing of the post-operative wound. Within 3 weeks wound was healed completely. Follow-up was done up to 10 months and patient had no any complaints or recurrence of warts. This case demonstrates that warts can be managed through Ayurveda without any complications, no recurrence and cost-effectively.